Documenting the Growth of Ultrasound Research in Emergency Medicine Through a Bibliometric Analysis of Accepted Academic Conference Abstracts. (15th April 2018) - Prats, Michael I.; Bahner, David P.; Panchal, Ashish R.; King, Andrew M.; Way, David P.; Lin, Stephen; Fox, J. Christian; Boulger, Creagh T.
Abstract : Objectives: Ultrasound (US) has become an indispensable skill for emergency physicians. Growth in the use of US in emergency medicine (EM) has been characterized by practice guidelines, education requirements, and the number of EM US practitioners. Our purpose was to further document the growth of EM US by profiling the breadth, depth, and quality of US‐related research presented at EM's most prominent annual research conference: the Society for Academic Emergency Medicine Annual Meeting. Methods: We reviewed published research abstracts from the annual Society for Academic Emergency Medicine conferences from 1999 to 2015. Abstracts related to US were identified and examined for the number of authors and rigor of the research design. Designs were categorized as experimental, quasiexperimental, and nonexperimental. Abstract submissions were analyzed by the average rate of change over time. Results: From 1999 to 2015, we observed a 10.2% increase in the number of accepted abstracts related to US research. This rate compared to a 3.2% average rate of change for all abstracts in general. The number of unique authors engaged in US research increased at a rate of 26.6%. Of the 602 abstracts identified as US related, only 12% could be considered experimental research. Conclusions: We observed larger increases in the number of US‐related research relative to the total number of abstracts presented at a national conference. The number of investigators engaging in this research has also steadily increased. The research design of these studies was found to be primarily quasiexperimental. To improve the quality of EM's use of point‐of‐care US, more rigorous research with experimental designs is needed.